ANALISIS PRODUK TABUNGAN WADIAH DAN MUDHARABAH DI BSI KCP MEDAN PULO BRAYAN - Maulida Jam’ah; Ahmad Amin Dalimunthe (Pusat Riset dan Inovasi Nasional, 2022)
This study focuses on the analysis of wadiah and mudharabah savings products at BSI KCP Medan Pulo Brayan. The purpose of this study was to analyze the wadiah and mudhaabah savings products and to determine the advantages and disadvantages of wadiah and mudharabah savings products at BSI KCP Medan Pulo Brayan. The research method is a descriptive qualitative research method. The object of this research uses secondary data data from literature studies such as books, journals, articles and so on. The data collection technique is observation. The results of the study show: 1) Analysis of wadiah and mudharabah savings products, which means wadiah savings are using a deposit scheme without profit sharing, while mudharabah savings, namely the owner of the funds, provide flexibility to the bank as a fund manager to use and benefit from a profit-sharing system. 2) And the wadiah and mudharabah savings products have advantages and disadvantages. The advantages of this product are the Deposit Insurance Corporation (LPS) and the lack of wadiah savings in the long term will harm customers, while the shortage of mudharabah savings is a monthly administration fee system.